Twelve-Factor application pattern with Spring Framework - Thakur, Dinkar; Kalia, Arvind (International Journal of Computer Sciences and Engineering, 2025)
The world of software development is moving from monoliths to micro-service architecture. Instead of having one big application, handling all tasks, there is a paradigm shift towards creating many small applications doing just a unit of work. When we build software-as-a-service we have to look into development, maintenance, and scalability of the application. Over the time it has been observed that the post development tasks of an application are inhibited because application is not just doing one task that it is supposed to do but all the activities that can be delegated. With twelve-factor pattern we can come close to create micro-services that can reduce cost of development, have maximum portability when deploying on different environment, are cloud ready and most importantly scale up. Spring.io provide a rich underlying framework, which can help in creating applications that are twelve-factor compliance, with Spring Boot they took it to a whole new level. With twelve-factor methodology in mind, in this research paper we will try to look into how spring can help covering each point in twelve-factors.